EMERGENCY TROLLEYS: AVAILABLE AND MAINTAINED, BUT ARE THEIR LOCATIONS KNOWN? – CLOSING THE LOOP - Ahmed A. Kolkailah; Sawsan Ghonaimy; Naomi Cassells; Allan Gillespie (European Scientific Journal, ESJ, 2014)
Emergency trolleys are developed and placed in strategic locations to improve the efficiency of the medical teams‘ response to emergencies. In order to close the loop on a previous audit, conducted a year earlier, a second survey was performed to assess the team of Anaesthetists‘ knowledge on the presence and location of those trolleys at the Victoria Ambulatory Care Hospital in Glasgow, Scotland. The results highlighted a considerable deficiency in the knowledge of those trolleys‘ locations, in both surveys. We suggest that similar surveys should be conducted as part of regular audits in all units and should include all staff involved in such emergencies. We also propose new approaches to tackle the problem and help improve the staff knowledge for quick and easy access; thus avoiding delays in critical care management.